The effect of the 4+1 planned writing and evaluation model on creative writing: An action research study - Karatay, Halit; Tezel, Kadir Vefa; Yazici, Emre; Goktenturk, Talha (EDUCATION ASSOC SOUTH AFRICA, 2023)
Writing is an important part of creative thinking as it is the reflection of a person's thoughts and reasoning. The aim with this study was to create a comprehensive and effective educational model that combines the teaching and practice of writing as a process and creative writing in a collaborative environment in the education of prospective language teachers. The study was designed with the convergent mixed method design. Quantitative data were obtained from the scoring of the first and final texts that the students were asked to write as part of the action plan implemented to improve the students' writing skills. Qualitative data consisted of the opinions of the participating students and the observations of the teachers who implemented the model. Through the aggregated analyses of these 2 types of data, the effect of the 4 + 1 planned writing and evaluation model (PWEM) on developing students' writing skills was determined. The results indicate that the model was useful, functional and improved the participating prospective language teachers' creative and process writing skills. The model enabled inexperienced writers to acquire metacognitive strategies, self-regulation, and self-efficacy that they would need in the writing process. This was supported by the opinions of the participating students and the observations of the teachers who implemented the model. The model may be used with any student population to help them to become self-sufficient in writing.
Keywords: 4+1 PWEM; attitude towards writing; creative writing; preservice teacher education; writing anxiety; MIXED METHODS RESEARCH; TEACHERS; INSTRUCTION; Education & Educational Research